The Product Analysis of Toba Caldera Geopark in Realizing Toba Regency Tourism Branding - M. Daud Siregar (Politeknik Pariwisata Medan, 2022)
This study aims to analyze existing tourism products in Toba Regency in realizing Toba Regency tourism branding. The research method used in this study is a qualitative method with descriptive analysis techniques. Research findings: (1). Nature is the main attraction in Toba Regency. (2). Existing tourist facilities in Toba district are adequate and meet the needs and desires of tourists. (3). Accessibility in Toba Regency has met the quality aspect, so it can provide security and comfort for tourists. Recommendations: (1) Toba Regency tourism branding, namely The Kaldera Toba Nomadic Escape Pesona Alam (2) It is necessary to do a better planning and development of the natural tourist attraction of Toba Regency. (3) There needs to be an increase in maintaining the beauty or preservation of nature which is quite beautiful in Toba district